AGING IMPAIRS AORTIC MITOCHONDRIAL FUNCTION AND ENHANCES INFLAMMATION AND PLAQUE NECROSIS IN ATHEROSCLEROTIC MICE. (11th November 2018) - Tyrrell, D
Abstract: Traditional murine models of atherosclerosis age with mild hypercholesterolemia and metabolic derangement. To examine if host age enhances atherogenesis independently of metabolic alterations, we induced hypercholesterolemia in wild-type (WT) aging mice using a PCSK9 adeno-associated virus and high-fat diet (HFD; 42% fat) feeding. Young (3-months) and aged (18-months) WT mice had similar blood cholesterol levels throughout the 10-week feeding period (1089 vs 1122 mg/dL, respectively). Fat mass was similar between young and aged mice (5.06 vs 4.88 g, respectively) and both groups gained the same amount of weight during the feeding period (10.9 vs 9.7 g, respectively). Glucose and insulin resistance measured via tolerance tests were dysregulated in both groups after HFD. There was no difference in total plaque size in the aortic sinus between the age groups (p=0.49); however, the atherosclerotic necrotic core size (p=0.04) and macrophage content was significantly greater in aged mice (p=0.002). Aged mice also had greater numbers of inflammatory monocytes in blood (p=0.004). Protein expression revealed that aged mice had significantly increased MyD88, IL-6, TNFa, PINK1, and Parkin expression in the aorta. High resolution respirometry revealed that aged mice had reduced aortic respiration compared to young atherosclerotic mice (p<.001). We conclude that aging induces inflammatory monocytosis and macrophage infiltration during atherosclerosis, resulting in increased plaque necrosis and progression of atherosclerosis, independently of confounding metabolic alterations. Possible mechanisms underlying these findings are increased age-related vascular inflammation and mitochondrial dysfunction during atherosclerosis progression.